Analisis Budaya Kerja Karyawan Pada Bank BRI Kanwil 1 Cabang Jakarta - Muhammad Ray Gildan; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2024)
This research uses a qualitative descriptive approach, namely the main data sources in qualitative research are words and actions. Words and actions are sources of data obtained from the field by observing or interviewing, by describing and analyzing the problems found. Qualitative research is based on primary data and secondary data. Primary data in this research was obtained by conducting observations, interviews, and documentation, while secondary data was obtained through books, previous research, and articles related to research. The aim of this research is to determine the work culture of employees at Bank BRI Regional Office 1 Jakarta Branch which includes the types of culture that exist, important elements of culture, cultural influences and current cultural analysis. From the results of this research, it can be seen that the culture at Bank BRI Regional Office 1 Jakarta branch adheres to Adhocratic Culture, which is a combination of the words 'Ad hoc' and bureaucracy.Therefore, organizations with an adhocracy culture are flexible and not hampered by bureaucratic procedures and policies. Researchers found that employee culture orientation refers to very high discipline caused by the family culture brought by the organization from the beginning of the company